TINJAUAN YURIDIS BAGI RUMAH SAKIT YANG MENOLAK PASIEN YANG TIDAK MAMPU - Agustina Anggraeni (Journal of Law ( Jurnal Ilmu Hukum ), 2019)
ABSTRACT            The state is an organization that has a purpose. In the context of the State of Indonesia, the purpose of the State is set out in the fourth paragraph of the Opening of the 1945 Constitution of the Republic of Indonesia which identifies the State of Indonesia as a State of law aimed at realizing public welfare. Every activity also must be oriented to the objectives to be achieved must also be based on the applicable law as a rule of state activities, government, and society. To achieve these national goals, a sustainable development effort is undertaken which is a series of comprehensive, directed, and integrated development, including health development.            In matters of public health, the government is obliged to ensure that its citizens are not sick and also obliged to fulfill the rights of their people to a healthy life and the implementation of conditions that determine people's health because health has become part of the lives of citizens, and to carry out the mandate the State must fulfill the health development principle as written in Article 2 of Law Number 36 the year 2009 concerning Health.            Poor health services will adversely affect the interests of the people who need medical services. Especially if the hospital does not provide proper services according to the procedures set out in the Criminal Code, which can cause patients to suffer losses that result in disability or death, then it is a criminal offense and can be criminalized according to Indonesian law.            Based on the background description of the problem above, the problems in this paper are: (1) How is the legal protection of poor patients as consumers of services in health services in hospitals? (2) What legal actions can be taken by incapacitated patients for the patient's rejection actions carried out by the hospital?             Based on the results of the study as stated above, the following conclusions can be drawn: (1) In an emergency, health care facilities, both government and private, are prohibited from rejecting patients and / or asking for advances. " besides, the act of refusing medical treatment is also a criminal act, so that it can be prosecuted criminally by following under Articles 304 and 531 of the Criminal Code. In the case of refusing hospital medical treatment, the hospital management responsible for violating the law, according to Article 190 paragraph (1) of Law Number 36 the Year 2009 concerning Health. (2) Civil legal action that can be taken by poor patients who are refused by the hospital in an emergency is by filing a breach of tort and unlawful actions. By rejecting poor patients in an emergency, the hospital has defaulted because it did not do what was agreed to do. In this case, the hospital does not do anything in the form of providing medical treatment to poor patients who are in an emergency of course require medical treatment as soon as possible. Provisions in Article 58 Paragraph (1) of the Health Law says that poor patients who are refused a hospital in an emergency can take legal action in the form of a civil claim by demanding compensation to the hospital that committed the refusal. Keywords: Patients, Services, Hospitals